The Relationship Between the Challenges of Academic Work and the Well-Being of University Lecturers in Light of a Qualitative Research in Hungary - Kocsis, Zsófia; Hrabéczy, Anett (Italian Sociological Review, 2026)
The changes in higher education as a result of the massification of higher education presented the society of educators with new challenges and roles. Previous research agrees that the effectiveness of higher education institutions depends to a large extent on the performance of the instructors, however, the examination of the factors that facilitate this and support well-being has received little attention in the literature so far. The aim of our research is therefore to explore the dimensions of the physical, mental, emotional and social well-being of instructors, and to reveal the factors that appear as challenges and risk factors during the work of teachers. To investigate this, we conducted a semi-structured focus group interview research, during which we interviewed 11 university instructors from Eastern Hungary. Among our most important results, it can be mentioned that the interpretation of the role as instructors at institutions of higher education, well-being at work, and the challenges associated with each role appear as significant factors in the narrative of the instructors. Our results can help educational policymakers and institutional decision-makers support the promotion of the well-being of educators with appropriate decisions, thereby indirectly promoting the achievement of educational and institutional excellence.